2010
DOI: 10.1021/es100919p
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Uranium(VI) by Pyrite under Boom Clay Conditions: Influence of Dissolved Organic Carbon

Abstract: The uptake of uranium(VI) by natural pyrite, FeS(2), was studied under conditions relevant for geological disposal of radioactive waste (anoxic atmosphere, approximately 0.014 mol.L(-1) NaHCO(3) electrolyte) with special emphasis on the role of dissolved organic matter. Solution analysis of batch experiments with different initial concentrations of uranium(VI) (10(-8)-10(-4) mol.L(-1)) was combined with X-ray absorption spectroscopy on the solid phase to elucidate the speciation of uranium in these systems and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
(64 reference statements)
3
41
0
Order By: Relevance
“…In Equation (13), T e [ρ(r)] is the kinetic energy of electrons, V ne [ρ(r)] is the nuclear-electron interaction, V ee [ρ(r)] is the Coulomb repulsion, and E XC [ρ(r)] is the exchange-correlation functional. The Kohn-Sham one electron orbital equations as a function of density are iteratively solved using a self-consistent field algorithm and the overall energy is minimized according to the variational principle.…”
Section: Dft or Wave Function Based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation (13), T e [ρ(r)] is the kinetic energy of electrons, V ne [ρ(r)] is the nuclear-electron interaction, V ee [ρ(r)] is the Coulomb repulsion, and E XC [ρ(r)] is the exchange-correlation functional. The Kohn-Sham one electron orbital equations as a function of density are iteratively solved using a self-consistent field algorithm and the overall energy is minimized according to the variational principle.…”
Section: Dft or Wave Function Based Methodsmentioning
confidence: 99%
“…These are radioactive materials, highly hazardous and lead to long term severe contaminations. Reduction process of these highly mobile and soluble actinyl ions are often catalyzed by the redox-active semiconducting minerals, for example iron sulfides (pyrite and mackinawite) [9][10][11][12][13] or oxides (hematite and magnetite) [9,12,14] present in the environment, in the presence of reductants, for instance, quinones, and Fe(II) species in solution, etc. Although the reduction process is a more complicated process and it was found that there were different mechanistic pathways were proposed depending on the reaction conditions and the presence of chelating ligands, for instance, hydroxyl, carbonate, chloride, and bicarbonate are available in the environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrite has already been identified as a medium for the uptake of U(VI) compounds by several authors. Bruggeman and Maes [14] reported the influence of dissolved organic carbon on the uptake of U(VI) by pyrite under Boom clay conditions. Results showed that the uranium solid-liquid distribution is governed by both reduction and adsorption processes under the experiments conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, chemogenic green rust and silicates including various micas as well as ferrous-bearing sulfide minerals such as galena and pyrite have been shown to adsorb and reduce U(VI) (Wersin et al, 1994;O'Loughlin et al, 2003;Ilton et al, 2004;Ilton et al, 2005;Ilton et al, 2006;Bruggeman and Maes, 2010).…”
Section: Introductionmentioning
confidence: 99%